Homicides in Sulaymaniyah Governorate – A Study in Population Geography - Hama, Asst.Prof.Dr.Srwa Jalal Hama (Sulaimani Journal for Humanities, 2025)
Human societies have witnessed social, economic, and political changes and transformations that have affected their populations. This transformation has been accompanied by the emergence of numerous problems, including a significant increase in murder rates. It is well-known that crime is a social phenomenon that occurs in diverse geographical areas, and its distribution has causes and motives that lead to spatial variations in geographical studies. This has prompted geographers to study the phenomenon of crime in all its spatial dimensions. This research examines the spatial distribution and temporal evolution of murders in Sulaymaniyah Governorate, given the importance of this topic in relation to community security and stability. This study aims to illustrate the spatial and temporal distribution of murders in Sulaymaniyah Governorate and to demonstrate the relationship between population growth and murders in the study area. It also aims to find appropriate solutions to combat or reduce crime and to identify the most prevalent types of murders in the governorate. As for the importance of this study, it presents a new approach by employing the principles of population geography as a tool and means to reach a final conclusion: diagnosing the causes and motives behind murder and the methods of criminal intervention in this crime. Due to the scarcity of geographical studies that shed light on the subject of crime, especially in Sulaymaniyah Governorate, this research focuses on studying murder as a social phenomenon and identifying the most important social and economic factors influencing the spatial variation of the crime. The aim is to develop a set of proposals that contribute to addressing this social phenomenon. Furthermore, the importance of the study is evident in the data, information, and statistics it will provide regarding murder in the governorate. The study employed descriptive and analytical methods to analyze the content of data issued by the Sulaimaniyah Court of Appeals, the Sulaimaniyah Personal Status Court (2015-2019), the Sulaimaniyah Governorate Police Directorate, Statistics Department, the Sulaimaniyah Governorate Police Directorate, the Anti-Crime Department and the Homicide Investigation Office, the Sulaimaniyah Governorate Statistics Directorate, population estimates for Sulaimaniyah Governorate (2015 and 2019), and the Sulaimaniyah Governorate Directorate for Combating Violence Against Women and Families. Geographic Information Systems (GIS) software was used to plot and represent crime data in Sulaimaniyah Governorate, correlate the data, and represent the results of the statistical analysis on a map. The Pearson correlation coefficient was also used, as there is a strong positive correlation between population size and the number of homicides, reaching 0.697 in 2019. The researcher also used the same correlation coefficient to find the relationship between population density and the number of crimes. (0.552) It has been established that there is a moderate direct relationship between them. The number of murders in Sulaymaniyah Governorate witnessed an increase during the study period from (91) murders in (2015) to (133) of the same type in (2019) for several reasons, including economic, political, security, social, and psychological factors. Security reasons may have an impact on the increase in the number of these crimes, such as the case of ISIS. The increase in the murder rate in Sulaymaniyah Governorate from (6.4) to (8.4) per (100,000) people for both the years (2015) and (2019) is attributed to the increase in population. The highest crime cases in Sulaymaniyah Governorate were in the (20-24) age group in (2019), reaching (32) murders, which is (24.1%) of the total murders in the governorate. This can be attributed This is due to the prevalence of the phenomenon of carrying unlicensed weapons or misusing weapons in general. Based on the study's findings, several recommendations were formulated, the most important of which is increasing attention to maintaining records and establishing a database specifically for crimes and their details. This facilitates access for specialists and researchers to statistics and data related to different types of crimes, allowing for in-depth study of the spatial and temporal variations of crime and identifying areas of concentration. It also increases the level of presence in monitoring the nature and causes of criminal phenomena in the study area within the governorate. This study was divided into six sections. The first section was dedicated to examining the nature of the relationship between geography and homicide. The second section addressed the temporal development of homicides in Sulaymaniyah Governorate and their geographical distribution for the period 2015-2019. The third section focused on the spatial distribution of homicides in Sulaymaniyah Governorate during the period 2015-2019. The fourth section... The fourth section examines the reality of murder in Sulaymaniyah Governorate according to age and gender demographics for the year 2019. The fifth section addresses population size and murder rates, while the sixth and final section discusses the causes of murder in Sulaymaniyah Governorate.